Informatization development of innovative technologies for processing polyester yarns - Сумская, Ольга Петровна; Домбровский, Андрей Геннадьевич; Домбровская, Елена Петровна; Полищук, Степан Александрович (Technology audit and production reserves, 2016)
The process of informatization of technological innovation of textile production – emulsifying polyester yarn is investigated by applying computerized color measurement systems and programs to meet the challenges of production coloristics in the production technology of finished products. Directions of increasing efficiency of technological processes is proved for production of the finished, painted under the specified standard polyester yarn by controlling the workflow in which the color is represented in digital form and can be adapted to the innovative technology of surface treatment of the textile substrate. The effect of emulsification process is investigated on the color characteristics of the painting coloration, obtained by dye class – Sumikaron on polyester yarns. It was found that treatment by Cololub 150 and Cololub C avoids dichroism of Sumikaron Red SE-RPD and Sumikaron Rubine SE-RPD dyes, and for Sumikaron Yellow SE-RPD dye, preliminary emulsifying polyester yarn causes increase the color intensity with increasing dye concentration on the fiber at high dyeing values (more than 3 %). It was found that for all dyeing made to emulsifying polyester yarn is observed a linear color change when changing the concentration of the dye, which is extremely important for more accurate color reproduction with automatic calculation of the formulations under standard dyeing. By using automatic calculation formulas and formed colorimetric data base and substrates treated by modern perspective emulsifiers, it is shown that considered innovative technologies are potential for cost reduction of dyed polyester yarn.